2020
DOI: 10.4038/sljb.v5i1.53
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analysis of some fruit peels and comparison of Lactic acid production by authochthonous Lactic acid bacteria using fruit peels

Abstract: 1. Introduction Fruit based industry produces a large volume of solid and liquid waste. These pose increasing disposal and pollution problems (high BOD or COD) and represents loss of valuable biomass and nutrients (Mridul&Preethi, 2014).Disposal of wastes from fruit-canning industries has been a problem due to high transportation costs and limited availability of landfills, as these byproducts carry no commercial value, they are often discharged in places they ought not to be disposed (Pradeep et al., 2014). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…However, higher yields were obtained by Bustamante et al [115], lactic acid production from orange peel yielding about 84% of lactic acid. However, lactic acid production by Lactobacillus plantarum using mango, banana and orange peels yielded 23.85%, 26.7% and 18.9% of lactic acid, respectively [116] which is lower than 79% lactic acid produced using pineapple waste by Aziman et al [114]. Other than lactic acid, pineapple residues have also been converted to succinic acid.…”
Section: Wine and Vinegarmentioning
confidence: 83%
“…However, higher yields were obtained by Bustamante et al [115], lactic acid production from orange peel yielding about 84% of lactic acid. However, lactic acid production by Lactobacillus plantarum using mango, banana and orange peels yielded 23.85%, 26.7% and 18.9% of lactic acid, respectively [116] which is lower than 79% lactic acid produced using pineapple waste by Aziman et al [114]. Other than lactic acid, pineapple residues have also been converted to succinic acid.…”
Section: Wine and Vinegarmentioning
confidence: 83%
“…The isolated strains from fruit peels were characterized microscopically as mentioned earlier (Arekemase et al, 2020). Thereafter, molecular identification was carried out to confirm the sequence of the ITS.…”
Section: Identification Of the Isolatesmentioning
confidence: 99%
“…The research of Maheshwari et al (2018) clearly revealed a high level of diversity in the Lactic Acid Bacteria (LAB) microflora from fermented fruit mixtures. Arekemase et al (2020) showed that lactic acid can be produced from mango, orange, and banana peels. Besides, the presence of bacterial or fungal colonies in orange, pineapple, banana and mixed fruit (pomelo, watermelon and melon) peels provided strong evidence that microbes produced cellulase in order to degrade carboxymethyl cellulose (CMC) (Chin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%